An analysis of syntactic translation error on communication students’ abstract in Universitas Bengkulu - Sri Rahayu Putri; Iis Sujarwati (Universitas PGRI Semarang, 2021)
This research was purposed to find out the syntactic translation errors from source language (Bahasa Indonesia) to target language (English) in communication students’ abstract of Universitas Bengkulu. The method that used by the researcher in this research was qualitative method along with content analysis approach. The error sources of translation were classified as morphological, lexical and syntactic error based on Sager’s theory. However, this research focused on the abstracts in thesis which made and translated by the communication students who’s graduated on 2019. The researcher found out that there were 52 syntactic errors occurred in 7 abstracts which became the object of this research